2018
DOI: 10.1111/nep.13081
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of sodium thiosulfate in treating calciphylaxis in chronic kidney disease patients

Abstract: Although the study was unable to assess the efficacy of sodium thiosulphate alone in the treatment of calciphylaxis, it still reveals a promising role of STS as an effective therapy for calciphylaxis. Further prospective studies to define the optimal therapy for calciphylaxis are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 44 publications
2
82
0
4
Order By: Relevance
“…The clinical characteristics at baseline were similar to those in the retrospective cohort recently described by Nigwekar et al, [16], but the mortality rate was twice as high in our patients (66 vs.35%) despite intensive care that combined sodium thiosulfate, dialysis intensification, surgical management, and/or hyperbaric oxygen therapy. Mortality was also higher than the median rate observed in published cohorts and case reports (see review by Peng et al [20]). The high death rate from cardiovascular causes (cardiac arrest or mesenteric infarction, n = 11/45, 24.5%) reflects the severity of systemic vascular disease in patients with CPX.…”
Section: Discussionmentioning
confidence: 67%
“…The clinical characteristics at baseline were similar to those in the retrospective cohort recently described by Nigwekar et al, [16], but the mortality rate was twice as high in our patients (66 vs.35%) despite intensive care that combined sodium thiosulfate, dialysis intensification, surgical management, and/or hyperbaric oxygen therapy. Mortality was also higher than the median rate observed in published cohorts and case reports (see review by Peng et al [20]). The high death rate from cardiovascular causes (cardiac arrest or mesenteric infarction, n = 11/45, 24.5%) reflects the severity of systemic vascular disease in patients with CPX.…”
Section: Discussionmentioning
confidence: 67%
“…Various modes of STS application in calciphylaxis have been reported: intravenous, intravenous during HD sessions, oral, intraperitoneal, intralesional, and topical. The optimal dose, regimen, and duration of treatment have not yet been established (4,5). Recent systematic reviews of treatment of uremic calciphylaxis with systemic STS have reported a significantly lower overall mortality rate of 38 to 50% (4, 21), compared to a 50 to 80% mortality rate after conventional treatment (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews of treatment of uremic calciphylaxis with systemic STS have reported a significantly lower overall mortality rate of 38 to 50% (4, 21), compared to a 50 to 80% mortality rate after conventional treatment (8,9). STS has several possible adverse effects, the most common ones reported being nausea, vomiting, and metabolic acidosis, followed by hypernatremia, headache, hypotension, and bone demineralization (4,22). With intra-dialytic application, a better patient survival rate and fewer problems with metabolic acidosis were reported compared to post-dialytic use (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations